Student Involvement Model in Laboratory Maintenance According to ISO 17025 - Muhsin, Muhsin; Ilhamdi, Mohammad Liwa; Wirandanu, Lalu Septiadi (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Student engagement in laboratory quality systems is essential for strengthening maintenance compliance and technical competence, particularly when aligned with international standards such as ISO 17025:2017. This study aims to (1) design a student engagement model that complies with the requirements of clauses 6.2.2 and 7.6 of ISO 17025:2017 and (2) analyze the impact of its implementation on improving equipment maintenance compliance and student technical competence. The research design employs an explanatory sequential mixed-methods approach, with a dominant quantitative component and qualitative support. The research subjects included 22 key informants (laboratory coordinators, laboratory heads, technicians, and students) who were selected with purposive sampling. Data were collected through structured questionnaires, in-depth interviews, FGDs, and participant observation. Quantitative data were analyzed using multiple linear regression using SPSS 25, while qualitative data were analyzed thematically. The results showed that the model designed based on four pillars: training, documented participation SOPs, internal audit simulations, and portfolio systems effectively transformed students from passive learners into competent contributors to the laboratory quality assurance system. The implementation of the model was proven to significantly improve maintenance compliance (mean = +1.81) and technical competence (mean = +1.59). Regression analysis confirmed that the model explained 80.2% of the variance in compliance (R² = 0.802) and 78.1% of the variance in competence (R² = 0.781), with documentation quality (β = 0.462; β = 0.423) as the strongest predictor. Qualitative findings revealed a shift in mindset from obligation to ownership as a key mechanism. This study concludes that the developed model not only aligns with ISO 17025 but also provides a strategic approach to building sustainable quality cultures in educational laboratories.